Parasitic contamination of lettuce: comparison between establishments located in areas with high and low economic values - Gustavo Trentini Barancelli; Larissa Kochenborger; Fernanda Gracieli Machado Brum; Fabiana Tonial; Cassiano Mateus Forcelini (ABCS Health Sciences)
Introduction: Diseases caused by contaminated food are a threat to public health. Lettuce (Lactuca sativa) is a widespread vegetable for human alimentation. Some systematic reviews showed parasitic contamination of lettuce in Brazil. Objective: To evaluate if the economic value of the places where lettuce is bought could be a determinant of parasitic contamination. Methods: We assessed the presence of parasites in the curly lettuces sold in the city of Passo Fundo, Brazil, and compared the frequency of contamination between markets and fruit stores, and between areas with high and low economic values. 130 samples of lettuce from 65 commercial establishments scattered throughout the city were washed with distilled water and analyzed under optical microscopy after 24 hours of spontaneous sedimentation method. Results: Parasitic forms were found in 80% of the samples, namely: ciliated cysts (probable Balantioides coli), larvae of nematode, Ascaris lumbricoides, cestode eggs, Giardia lamblia, Hymenolepis nana, Entamoeba coli, and Fasciola hepatica. Contamination by larvae of nematode was more frequent in fruit stores than in markets (35.9% vs. 19.7%; p=0.039). Areas with high and low economic values had the same frequency of contamination, but there was a trend to higher contamination by cestode eggs in areas with low economic values. Conclusion: This study was the first to show that the frequency of parasitic contamination is not different compared to establishments located in areas of high and low economic values, refuting any common sense that regions of the city with higher income are less exposed to parasitic contamination of food.